Penggunaan Media Audio Visual Pada Pembelajaran Fiqih Untuk Meningkatkan Prestasi Belajar Siswa Kelas VIII di MTs Nurus Salam - Puspita Rahmadani; Khairuddin Lubis; Hotni Sari Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the role of dhikr activities in developing emotional regulation among female students (santriwati) at Pondok Pesantren Darul Mukhlisin Serdang Bedagai. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The findings indicate that regular dhikr practice, both after obligatory prayers and at specific times, plays a significant role in helping students manage negative emotions such as anger, anxiety, and stress. Teachers and dormitory supervisors observed that students who consistently engage in dhikr demonstrate greater patience, discipline, and higher learning motivation. The study concludes that dhikr is not merely a ritual act of worship but also serves as an effective Islamic psychotherapeutic medium to enhance inner peace and build positive character among students.